Rolandic Epilepsy: A literature review (Research, Society and Development, 2024)
Epilepsy is a medical condition in which there is disturbance of brain activity, characterized by focal, unprovoked or reflex seizures. The objective was to discuss the diagnosis and evolution of Rolandic Epilepsy in childhood, syndromic characteristics and pharmacological therapeutic options. Material and method: integrative literature review using the SCIELO, PUBMED and UPTODATE databases, between 2012 and 2022. 69 articles were identified, being 22 used in the preparation of the work. The results show that Rolandic Epilepsy is the most common neurological disorder in childhood, among other epileptic syndromes, males are the most prevalent and the first manifestation usually occurs before puberty, between seven and nine years of age. The evolution of the clinical history helps in early diagnosis, which represents the best strategy to indicate the correct treatment and avoid future complications of childhood neurodevelopment. For this, the specific test is the electroencephalogram, the result of which reveals obvious abnormalities such as sharp centrotemporal waves and abnormal morphological findings. The prognosis for Rolandic Epilepsy is favorable, due to the self-limited nature of the disease; in most cases, seizures remit before adulthood without causing major damage to the child's neurological development.